Between Sunnah Currency and Sufi Doctrine: Mediating and Negotiating the Gold Dinar and Silver Dirham on Digital Platforms by the Indonesian Murabitun - Rizqa Ahmadi; Wildani Hefni; Muhammad Muntahibun Nafis (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2022)
The Murabitun World Movement promotes the gold dinar and silver dirham as authentic Islamic currency tools. However, their vision of establishing an independent Islamic currency is rejected by the socio-political dynamics of the communities’ home countries. Using Talal Asad’s theory of Islam as a discursive tradition, the study investigates the local practices of the Murabitun among Indonesian Muslims, with particular attention to their cultural identity. This study relies much on online data and cyber resources. The Indonesian Murabitun actively promoted the circulation of the gold dinar and silver dirham as an Islamic currency at the Pasar Muamala (exchange market) in Madiun and Yogyakarta. The Indonesian Murabitun movement was initially established in Depok, West Java by Zaim Saidi with his creation of the Pasar Muamala. After Zaim Saidi was formally charged with violating the currency law, his movement lose much its influence. However, utilizing the dynamics of the socio-political landscape this movement has continued to be actively involved in promoting the gold dinar and silver dirham currency—as an alternative transaction tool alongside the regular currency—on digital media platforms.